Impact of the Non-Muslim Population on the Islamic Bank of Indonesia in Jayapura, Papua - Kambuaya, Quinci Fransiska; Prahatnasari, Riskyana Tiara Dewi; Annisa, Uchi Nur; Satriyo, Daiva Arkana Kautsar (AIBPM Publisher, 2024)
The purpose of this research is to assess the attitudes of non-Muslims in Jayapura, Papua towards the Islamic Bank of Indonesia. The population studied is the non-Muslim population of Kecamatan Jayapura Utara, Papua Province. This study includes 123 samples from respondents. Research results indicate that location, product, and promotion have a significant impact on the attitudes of non-Muslim populations toward Bank Syariah Indonesia.